Nutritional quality, fruit shape and relationships among exotic and local Capsicum pepper genotypes in Uganda - Asiimwe, S.; Ochwo-Ssemakula, M.; Ssekkadde, P.; Ribeiro, C.; Karungi-Tumutegyereize, J. (International Journal of Horticultural Science, 2021)
Twenty-one hot pepper genotypes comprising of local (15) and exotic (6) types (C. annuum, C. frutescens and C. chinense) were characterized for selected fruit traits after propagation in a glasshouse at the Makerere University Agricultural Research Institute Kabanyolo in Central Uganda using a completely randomized design with three replicates. Ripe fruits were harvested and analyzed; traits evaluated were all significantly different at P